Probing outflows from young stars and brown dwarfs - Whelan, Emma Teresa (Trinity College (Dublin, Ireland). School of Physics, 2005)
The phenomenon of mass outflow from young stellar objects, is arguably the most spectacular stage in the formation of a star. Much is known about the large scale manifestations of outflows and many breathtaking images attest to the energetic nature of their interactions with their parent molecular clouds. However, in comparison to what is known on the large-scale, the mysteries of the central engines of young stars from which the outflows are launched, are little understood. A lot of the knowledge concerning protostellar jets close to their point of origin (the jet launch region) comes from the study of the forbidden emission lines (FELs) of one group of protostars in particular, the low mass optically visible Classical T Tauri stars. Traditionally probing the region of the central engine has proved difficult. Direct imaging for example is challenging due to contamination by stellar radiation. Intermediate resolution spectroscopy helps to overcome this problem however the spatial resolutions achievable are not satisfactory. If a true understanding of the central engine is to be attained information must be recovered on the smallest scales possible.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin